PERAN ORANG TUA DALAM PENDIDIKAN ANAK DIRUMAH - Setiani, Nurul; Halimah, Halimah (Batara Wisnu : Indonesian Journal of Community Services, 2024)
In this community service, a qualitative and descriptive research approach is used. The data source used was interviews with Narsum, and the data was evaluated using a descriptive analysis approach. This finding concerns the role of parents, especially single parents, in raising their children. Children’s education is an important part of children’s development. One of the key factors in a child’s educational success is the role of parents. In this community service, the focus is more on the role of single parents in children’s education at home. Apart from working, single parents must also be able to divide their time with their child. Roles also include various behaviors, tasks, and functions that a person is expected to perform in activities or social interactions. For example, in a family context, a parent’s role includes providing love, protection, and guidance to their children, while in a work context, a manager’s role may include decision making, organizing resources, and mentoring subordinates